Anterior Cervical Decompression and C5 Palsy: A Systematic Review and Meta-analysis of Three Reconstructive Surgeries. Issue 22 (15th November 2020) - Takase, Hajime; Tayama, Katsuko; Nakamura, Yoshihiko; Regenhardt, Robert W.; Mathew, Justin; Murata, Hidetoshi; Yamamoto, Tetsuya
Abstract : Study Design: A systematic review and meta-analysis were performed with the literature including the case of C5 palsy following anterior cervical decompression surgery. Objective: The aim of this study was to compare three reconstructive procedures of anterior cervical decompression, the incidences of delayed C5 palsy and other complications were assessed. Summary of Background Data: Delayed C5 palsy is now a well-known complication after cervical decompression surgery. The etiology of C5 palsy has been studied, especially after posterior surgery. However, in anterior surgery there has been a lack of investigation due to procedure variation. Additionally, limited evidence exists regarding the risk of C5 palsy in surgical procedures. Methods: We performed an extensive literature search for C5 palsy and other complications with ACDF, ACCF, and their combination (Hybrid). Gross incidences of C5 palsy after these three procedures were compared, and specific superiorities (or inferiorities) were investigated via comparison of binary outcomes between two of three groups using odds ratios (OR). Results: Twenty-six studies met the inclusion criteria. A total of 3098 patients were included and 5.8% of those developed C5 palsy. Meta-analyses demonstrated that ACDF had a lower risk of palsy than ACCF (OR 0.36, 95% confidence interval [CI] 0.16–0.78), whereas ACDF versus Hybrid (OR 0.60, 95% CI 0.24–1.51) and Hybrid versus ACCF (OR 1.11, 95% CI 0.29–4.32) were not significantly different. Although these differences were not observed in shorter lesion subgroups, there were significant differences between the three procedures in longer lesion subgroups ( P = 0.0005). Meta-analyses revealed that in longer lesions, ACDF had a significantly lower incidence than ACCF (OR 0.42, 95% CI 0.22–0.82). Additionally, Hybrid surgery was noninferior for palsy occurrence compared to ACCF, and suggested a trend for reduced rates of other complications compared to ACCF. Conclusion: ACDF may yield better outcomes than Hybrid and ACCF. Furthermore, Hybrid may have advantages over ACCF in terms of surgical complications. Level of Evidence: 3 Abstract : Supplemental Digital Content is available in the textA meta-analysis was performed to investigate advantage in terms of C5 palsy between anterior cervical procedures. ACDF is associated with lower risks, especially in regard to treatment of longer lesions. In the severe case, Hybrid surgery might be a reasonable alternative to ACCF given an improved side effect profile.